Identifikasi Depresi Postpartum Menggunakan Edinburgh Postnatal Depression Scale di RS Tk II Udayana - Serinadi, Desak Made (JURNAL MEDIKA USADA, 2025)
Background: Postpartum depression has become a common condition that is often unnoticed in its onset. Postpartum depression can become more severe if not detected and managed adequately.Objective: This study aims to identify postpartum depression using the Edinburgh Postnatal Depression Scale (EPDS) at RS Tk II Udayana.Method: The research design uses a quantitative approach, specifically descriptive with a cross-sectional approach. The sample of this study consisted of 30 respondents selected using the accidental sampling technique. Data analysis was conducted using descriptive analysis.Results: The results of the descriptive test found that the education level was high school for 20 people (66.7%), in early adulthood for 26 people (86.7%), gravida 1 for 14 people (46.7%), and housewives for 15 people (50%). The identification of postpartum depression found that the majority of postpartum mothers respondents experienced mild depression, with 28 individuals (93.3%) and 2 individuals (6.7%) experiencing moderate depression.Conclusion: The conclusion of this study is that almost all respondents experienced mild depression. The research results indicate that almost all postpartum mothers are at risk of experiencing more severe depression if early detection and further intervention are not carried out.